Analytical review and prospects of research in the field of small hydroenergetics and hydroenergetic potential of Ukrainian rivers - Obodovskiy, O.; Kryvets, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main directions and analysis of research in the field of hydropower and hydropower potential of Ukrainian rivers are established. A brief review of the classification of small hydropower plants is given. Estimates of hydropower potential of rivers are considered. The ecological aspects of the use of hydropower potential of rivers are highlighted. Tendencies of development of Ukrainian power engineering and, in particular, hydropower are analyzed. The role of "green" tariff for electric energy produced by small hydropower is shown. The role of "Energy Strategy of Ukraine for the period up to 2030" in the field of small hydropower is highlighted. The methodical approaches to environmental impact assessment in the construction of small hydropower plants are characterized. The prospects for using the hydropower potential of Ukrainian rivers and a proposed new technological paradigm for the development of small hydropower in Ukraine was assessed.
Keywords: methodological approaches to formation of small hydroenergetics; assessment of hydroenergetic potential of Ukrainian rivers; ecological aspects of hydroenergetic potential of rivers; small hydro energy resources and their types; High-tech small hydroelectric power plants and their efficiency